Interaction between clock genes, melatonin and cardiovascular outcomes from ICU patients - Jose M. Jiménez-Pastor; Ignacio Morales-Cané; Francisco J. Rodríguez-Cortés; Luna López-Coleto; Rocío Valverde-León; Pedro Arévalo-Buitrago; María J. Medina-Valverde; Carmen De la Fuente-Martos; Darío Acuña-Castroviejo; Miguel Meira e Cruz; Raúl M. Luque; André Sarmento-Cabral; et al. (Intensive Care Medicine Experimental, 2025)
Abstract Background Circadian rhythms, driven by biological clocks, help organisms align their physiological functions with environmental changes, promoting homeostasis. The central clock in the suprachiasmatic nucleus coordinates peripheral clocks via neurohumoral feedback involving proteins like CLOCK, BMAL1, CRY 1/2, and PER 1–3. In the ICU, these circadian processes often face disruptions from constant lighting, noise, and irregular sleep–wake cycles, impairing sleep quality and worsening stress responses. These disruptions can lead to adverse clinical effects, including higher cardiovascular complication rates. This study examines how ICU stays affect circadian rhythm regulators and their association with cardiovascular outcomes. Results Significant differences were identified in melatonin levels and the expression of BMAL1, PER1, RORA, and NR1D1 between ICU stays of ≤7 days and >7 days. The APACHE-II severity scale influenced melatonin and the expression of CLOCK, PER2, CRY2, and RORA. Nonlinear relationships were observed between melatonin, clock genes, heart rate, and blood pressure (systolic and diastolic). In certain groups, molecular and physiological data showed correlations exceeding 90%. Conclusions These findings highlight a robust association between circadian disruption, as measured by melatonin and clock genes, and cardiovascular physiological rhythms in ICU patients.